PENGARUH PENGGUNAAN MEDIA AUDIO TERHADAP KETERAMPILAN MENYIMAK CERITA ANAK DI SEKOLAH DASAR - Sitorus, Pangihutan; Margiati, Margiati; Kaswari, Kaswari (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe problem in this thesis is "How is the influence of audio media on the skill of listening to the story of the students of grade V students of State Elementary School 30 in South Pontianak?".Aims to analyze how much influence the use of audio media to the skills of listening to the story of the students of grade V students of State Elementary School 30 Pontianak Selatan. The research method used is experimental method. The research used Pre-experimental design with one-group pretest-postest design. The population in this study is all students of class V State Elementary School 30 Pontianak Selatan which amounted to 40 people. The sample in this research is all students of class V State Elementary School 30 Pontianak Selatan which amounts to 40 people. Data collection techniques used are measurement techniques. Data collection tool used in the form of test and photo documentation. Based on the data analysis, the average listening skill of students before using the audio media is 77,664 and the average listening skill of students after using audio media equal to 85,99675. The result of t test obtained by t_tabel at significant level Î± = 5% is 1,684. Because t_hitung (16,339)> t_tabel (1,684) then hypothesis testing of post-test data is accepted. Results effect size of this study amounted to 0.8 (high category). That is, the audio media affect the skills of listening to the story of the students of class V students of State Elementary School 30 Pontianak Selatan.Â Keyword: Influence, Audio Media, Childern Story, Listening Skill